Acclimation of sugar beet in morphological, physiological and BvAMT1.2 expression under low and high nitrogen supply. - Jiajia Li; Wangsheng Li; Lingqing Xu; Man Wang; Wanting Zhou; Siqi Li; Wenbo Tan; Qiuhong Wang; Wang Xing; Dali Liu (PLoS ONE, 2022)
Understanding the response and tolerance mechanisms of nitrogen (N) stress is essential for the taproot plant of sugar beet. Hence, in this study, low (0.5 and 3 mmol/L; N0.5 and N3), moderate (5 mmol/L; N5; control) and high (10 and 12 mmol/L; N10 and N12) N were imposed to sugar beet to comparatively investigate the growth and physiological changes, and expression pattern of the gene involving ammonia transporting at different seedling stages. The results showed that, different from N5 which could induce maximum biomass of beet seedlings, low N was more likely to inhibit the growth of beet seedlings than high N treatments. Morphological differences and adverse factors increased significantly with extension of stress time, but sugar beet seedlings displayed a variety of physical responses to different N concentrations to adapt to N abnormal. At 14 d, the chlorophyll content, leaf and root surface area, total dry weight and nitrogen content of seedlings treated with N0.5 decreased 15.83%, 53.65%, 73.94%, 78.08% and 24.88% respectively, compared with N12; however, the root shoot ratio increased significantly as well as superoxide dismutase (SOD), peroxidase (POD), glutamine synthetase (GS) activity and malondialdehyde (MDA) and proline content, especially in root. The expression of BvAMT1.2 was also regulated in an N concentration-dependent manner, and was mainly involved in the tolerance of beet leaves to N stress, which significantly positively correlated to GS activity on the basis of its high affinity to N. It can be deduced that the stored nutrients under low N could only maintain relatively stable root growth, and faced difficulty in being transported to the shoots. Sugar beet was relatively resilient to N0.5 stress according to the mean affiliation function analysis. These results provide a theoretical basis for the extensive cultivation of sugar beet in N-stressed soil.